Unemployment In The Two Decades Of Post-Reform (Study Cases in the West Java Province, 2002 – 2022) - Ramdhani, Harri; Rohadin, Rohadin (Universitas Wiralodra, 2025)
Objective study This is For analyze factors that influence the Open Unemployment Rate in West Java in term long ( for 20 years ) namely post reform until moment this . While background behind study This is For to reveal phenomenon unemployment educated , namely phenomenon height level unemployment that is not caused by the level low education . Phenomenon This show level unemployment the more tall precisely when level education the more high . Research done with method analysis quantitative that is with analysis regression multiple . In simultaneous (F test), variable free researched that is Regional Minimum Wage (UMR), Rate Growth Economy (LPE), Number of Workforce ( AK) and Average Length of Schooling (RLS) have an influence to variable bound ( Open Unemployment Rate /TPT). However in a way partial (T-test), only There is two influential variables in a way significant to the Open Unemployment Rate (TPT), namely Number of Workforce ( AK) and Average Length of Schooling (RLS). Variables Number of Workforce own Beta coefficient is negative which means the more high Labor Force (AK) then the more low Open Unemployment Rate (TPT). On the other hand , the Average Years of Schooling (RLS) variable shows number positive which means the more tall The Average Length of Schooling (RLS) figure then the Open Unemployment Rate (TPT) continues to rise. Research results This to reveal phenomenon unemployment educated people that occur in Indonesia.